DESIGN OF A LOW-COST AUGMENTATION NAVIGATION SYSTEM: THE UNITED KINGDOM’s IMMEDIATE ANSWER TO THE GALILEO BREXIT CONUNDRUM - Lawal, Lasisi Salami; Chatwin, Chris Reginald (IJRDO - Journal of Electrical And Electronics Engineering, 2019)
United Kingdom’s Brexit from the European Union implies restricted access to the European Global Navigation Satellite System (GNSS) System - Galileo; with no access to the secured and encrypted signal used for defense and government purposes, which is restricted to European Union (EU) members. To mitigate this issue, the United Kingdom can, as a matter of urgency, launch a payload on a national military Communications Satellite to provide Navigation Overlay Services for the United Kingdom territory, surrounding waters and neighboring ally countries to meet the requirements of: Defense systems, Aviation, Maritime requirements and the effectiveness of Location-based Services for Emergencies and Crisis management etc. This paper describes the design of a navigation overlay service system as a hoisted payload on a national satellite and the required supporting ground infrastructure, highlighting various applications, services and solutions.